Does Auditor Tenure Reduce Audit Quality? - - Junaidi; Setiyono Miharjo; Bambang Hartadi (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
Reduced auditor independence and the rise of corporate accounting manipulations have caused trust of the users in audited financial statements to begin to decline, so users of financial statements are questioning whether public accountants are independent parties. This research issue is related to the Decree of the Minister of Finance No. 17 in 2008 about public accountant services. Giving attestation services, in the form of financial statements about an entity, are conducted by the audit firm for no longer than 6 consecutive fiscal years and by a public accountant for 3 consecutive fiscal years at the longest. The purpose of this research is to examine empirically the influence of auditor tenure on audit quality. Auditor tenure is measured as the length of the auditor-client relationship. Audit quality is measured by the propensity of auditors to issue a going-concern opinion. This study uses a sample of firms listed on the Indonesia Stock Exchange during the 2003-2008 period. Research analysis uses logit model to measure the effect of auditor tenure on the auditors’ propensity to publish a going-concern opinion. The hypothesis which states that the length of auditor tenure influences negatively the propensity of auditors to issue a going-concern opinion is statistically supported. This research is expected to provide empirical evidence about the importance of limiting of the auditor-client relationship.